1051 Assessment of asymptomatic severe aortic regurgitation by doppler-derived echo indices: comparison with magnetic resonance quantification. (17th January 2020) - Hlubocka, Z; Linkova, H; Praveckova, A; Polednova, A; Dostalova, G; Blaha, M; Maly, J; Penicka, M; Linhart, A; Kockova, R
Abstract: Funding Acknowledgements: This study was supported by Ministry of Health of the Czech Republic 17-28265A Introduction: Management of asymptomatic patients with chronic severe aortic regurgitation (AR) is challenging. Reliable quantification of the AR severity is essential. Transthoracic echocardiography (TTE) is a primary imaging modality. Grading of AR severity is achieved by an integrative approach. Cardiovascular magnetic resonance (CMR) can directly quantify AR severity by measuring regurgitation volume (RV) and regurgitation fraction (RF). Purpose: There are few data on direct comparison between TTE and CMR for quantification of AR. Our study aimed to compare quantitative and indirect echo-Doppler indices to quantitative MRI derived parameters in asymptomatic patients with severe chronic AR. Methods: In a prospective three-centre study, we evaluated patients with moderate to severe (3+) and severe (4+) chronic AR using TTE and CMR. All patients were asymptomatic, without indication for surgical treatment. The severity of AR was graded using TTE multiparametric approach. A 2-D and 3-D TTE were performed with an assessment of left ventricle size and function, valve morphology, Doppler parameters of AR including vena contracta width, diastolic flow reversal velocity in descending aorta, RV, RF using volumetric method, 3D-vena contracta area (3D-VCA). The CMR quantified left ventricle volumes and function, RF and RV using the phase-contrast velocity mapping. All imaging studies were analysed in CoreLab. Results: A total of 104 patients were enrolled during 2015-2018. Mean patient age was 44 ± 13 years, 89 patients (86%) were males and 83 patients (81%) had a bicuspid or unicuspid aortic valve. Using the TTE severe (4+) AR was present in 48 (46%) and moderate to severe (3+) AR in 56 (54%) individuals. Concordant grading of AR severity with both techniques was observed in 77 (74%) patients. An integrative TTE approach showed a trend to underestimate AR severity. The best correlation between echo-Doppler indices and CMR measured RV and RF was found in two parameters: diastolic flow reversal velocity in descending aorta ( Rs = 0, 62, p < 0, 0001 for RV, Rs = 0, 50, p < 0, 0001 for RF) and 3D-VCA (Rs = 0, 48 for RV, p < 0, 0001, Rs = 0, 38 for RF, p < 0, 0001). On the contrary vena contracta width showed poor correlation with CMR (Rs = 0, 18, p = 0, 07 for RV and Rs = 0, 11, p = 0, 29 for RF). Correlation between quantitative parameters of AR assessed by TTE volumetric method and CMR technique was modest (Rs = 0, 40 for RF and Rs = 0, 50 for RV, p < 0, 0001), 95% confidence intervals were wide. Good correlation between TTE and CMR were found for LV dimensions, volumes and ejection fraction. Conclusion: Out of indirect Doppler-echo indices of AR severity, diastolic flow reversal velocity in descending aorta and 3D-vena contracta area showed the best correlation with MRI derived RF and RV in patients with chronic severe AR. Quantitative parameters of AR (RF and RV) assessed by echo volumetric method had an only modest correlation to RF and RV measured using CMR.